Agama dan Cakupan Ilmu Agama Menurut W.B. Sidjabat - Permata, Intan (UIN Sunan Kalijaga Yogyakarta, 2019)
This article examines the ideas of W.B. Sidjabat on the study of religion which is hardly discussed by scholars. Most scholars focus their studies more on the thoughts of Mukti Ali, Rasyidi, and other comparative religious figures, whereas Sidjabat tends to be more objective in building the paradigm of religious science. According to Sidjabat, religion is a neutral scope of study so that a religious researcher must not be subjective in his research and use several methodologies. Likewise with the perspectives used, so the methodology used in religious research will be relevant to the scope of religious studies. Thus, the study of religion aims to build a close personal relationship between religions, foster religious ethics among religious communities, deepen knowledge about the teachings of other religious communities, and stimulate cooperation among religious believers in practice.